Identitas nasional: Konsep, tantangan, dan strategi memperkuatnya di era globalisasi - MAULANA, RAFLY (Maliki Interdisciplinary Journal, 2025)
National identity is an important element that distinguishes one nation from another and serves to unite a society that has diversity. In Indonesia, there is a nationality that is reflected in the principles of Pancasila, the motto Bhinneka Tunggal Ika, and the use of the Indonesian language. The name, the global identity of the world, the identity of the nation’s people are interrelated with each other, they are the main ones, they are technologically, socially, and economically advanced. To strengthen national identity, several steps can be taken, such as strengthening national education, utilizing technology to advance local culture, preserving cultural heritage, and developing an economy based on local potential. Through these efforts, national identity is expected to remain maintained and relevant even in an increasingly globally connected world.